Pillarization of layer double hydroxides (Mg/Al) with keggin type K4[α-SiW12O40]•nH2O and its application as adsorbent of procion red dye - Intan Permata Sari; Muhammad Said; Aldes Lesbani (Science and Technology Indonesia, 2017)
Pillarization of layered double hydroxides with polyoxometalate K4[α-SiW12O40]•nH2O at various times i.e. 3, 6, 9, 12, 24, 36 and 48 hours has been done. The pillared product was characterized by FT-IR spectrophotometer and XRD. The optimum pillared layered double hydroxides of polyoxometalate K4[α-SiW12O40]•nH2O was used as an adsorbent of procion red dye. The results of characterization using FT-IR spectrophotometer is not yet show the optimum pillarization process. The characterisation using XRD the successfully of pillared layered double hydroxides of polyoxometalate K4[α-SiW12O40]•nH2O showing the existence of diffraction angle 8.5o with intensity 355. Furthermore, the pillared layered double hydroxides of polyoxometalate K4[α-SiW12O40]•nH2O with time variation of 12 hours was applied as an adsorbent of procion red dye. The results show the adsorption rate was 0.523 min-1, the highest of absorption capacity at 70oC was 10.8 mol/g, the highest energy of absorption 70 oC was 125 kJ/mol. The enthalpy (∆H) and entropy (∆S), decrease as the increasing concentration of procion red dye. Keywords: layered double hydroxides, polyoxometalate, pillaration, procion red, adsorption